Peningkatan Hasil Belajar Matematika Kelas VI Menggunakan Model Problem Based Learning (PBL) Pada Materi Bangun Ruang - Sari, Nina Indra; Firdaus, Fery Muhammad; Jabar, Cepi Safruddin Abd (Jurnal Ragam Pengabdian, 2026)
This study is a Classroom Action Research (CAR) that aims to improve mathematics learning outcomes in spatial geometry through the application of the Problem Based Learning (PBL) model in grade VI of SD Islam Terpadu Baiturrahman Buntok, South Barito. The study was conducted in two cycles, each of which included planning, implementation, observation, and reflection stages. The research subjects consisted of 27 students. The background of this study was the low student learning outcomes, where only 40% of students achieved the Minimum Completion Criteria (KKM) with an average score of 62, below the standard of 70. Learning that is still teacher-centered and the lack of use of contextual problems are contributing factors. Data collection techniques include observation, questionnaires, tests, and documentation. The results of the study showed an increase in student activity from 66.66% in cycle I to 74.07% in cycle II. Learning outcomes also increased from 71.76% in cycle I to 83.33% in cycle II. These findings indicate that the application of PBL is effective in improving student learning outcomes and activity in mathematics learning.